Intensive nursing management for a patient with sepsis treated by continuous renal replacement therapy (1例脓毒症患者连续肾脏替代治疗的集束化护理体会) - ZHANG Mengmeng (张梦梦); RU Jiangli (茹江丽); LI Jing (李静) (Association of Integrative Nursing, 2022)
This paper summarized the intensive nursing management for a patient with sepsis treated by continuous renal replacement therapy (CRRT). Clustered nursing interventions were carried out by sub-specialist group nursing management, and targeted nursing measures were taken to prevent the complications and improve the prognosis of the patient. (本文总结1例脓毒症患者开展连续肾脏替代疗法(CRRT)治疗的集束化护理经验, 运用集束化护理干预策略, 通过亚专科小组护理管理模式, 制定相应的护理措施, 积极预防并发症, 改善患者预后。)